Diversity of nitrogen fixing bacteria associated with slope grass axonopus compressus / Alazhar Hassin - Alazhar, Hassin (2011)
Vegetation cover, especially grasses, is proven to have a significant contribution for slope stabilization. Nitrogen fixing bacteria supply some amounts of nitrogen (N) required by slope grasses for proper growth and development. In this study, three slopes were chosen based on their soil strengths namely slope A (130-140 kPa), B (80-100 kPa) and C (50-70 kPa). This study showed that the more stable slopes will also have a lower soil saturation level. There was a positive relationship between sizes of bacterial populations with soil saturation level (r2 = 0.60, p<0.05). Similar correlations were also observed between soil shear strength with soil saturation levels ( r2 = 0.58, p<0.05) as well. Culturable nitrogen-free living bacteria were isolated and enumerated from roots of Axonopus compressus, a slope grass using Burk’s nitrogen-free medium. The diversity of free-living nitrogen fixing bacteria was initially determined by the REPPCR and ERIC-PCR fingerprinting method. Results indicated that REP-PCR give better variable. Hence, the method was used throughout the study. Dendograms were constructed from REP-PCR profiles of a total of 31 strains. The cluster analysis indicated that the diversity of nitrogen-fixing bacteria on the grass roots was quite high and closely related among the population. The information about the presence of nitrogen-free fixing bacteria will greatly assist future management of vegetation to stabilise slopes.